Migrations: interdisciplinary perspectives - Schroeder, Renee; Wodak, Ruth; Messer, Michi (Springer Vienna, 2012)
In contemporary Europe and beyond, the concept of "migration" has acquired multiple distinct meanings. The range of reactions to migrants depends on the country of origin, their "symbolic capital" (education, professional background, language skills) as well as on aspects of gender, religion, cultural tradition, and social class. Various legal regulations on citizenship and employment are currently being debated and implemented across Europe, fuelled by a "politics of fear" propagated by mainstream and populist parties alike. Counter-discourses are rare and limited. This volume incorporates contributions from the international symposium "Migrations: Interdisciplinary Perspectives" (2010), covering the following topics: peer relations among immigrant adolescents; migration, identity, and belonging; ego documents and migration histories; the concept of diffusion in the natural sciences; media coverage of migration; migration and genes.